Challenges Facing Mexican Students in the United Kingdom: Implications for Adaptation During the Early Stage - Hernández López, Elizabeth Margarita (Journal of International Students, 2020)
This article reports data drawn from a doctoral qualitative case study conducted during the 2016–2017 academic calendar. The study explored the academic, sociocultural, and affective challenges a cohort of Mexican postgraduate international students faced during their first 2 weeks at a university in England. Twenty students participated in three focus groups, while seven were involved in in-depth interviews. The findings support the notion that the adaptation experiences of Mexican postgraduate international students in the United Kingdom are like those of other groups of overseas students. They undergo an extensive array of challenges related to the perceived extent of cultural distance and differences in individual and societal characteristics, as outlined by Ward et al. (2001). Concerning the early stage, findings did not seem to support traditional views of culture shock (Adler, 1975; Lysgaard, 1955; Oberg, 1960).